Analisis Kebutuhan Tenaga Perawat di RSUD dr. Soedono Madiun - Ayu Nur Malasari; Nyoman Anita Damayanti; Kantrey Sugiarto (Jurnal Keperawatan Silampari, 2021)
This study aims to materialize human resource planning, especially in nursing, to get an effective and efficient workforce. This research method is a literature study of several theories of calculating the number of nursing staff using the Nina formula method and the Ilyas method. The results of the study, based on the calculation of the Nina Formula method, the number of nurses needed by dr. Soedono Madiun with a BOR rate of 66.19% is 775 people. Based on the analysis of the Ilyas Formula method, the number of nurses required by dr. Soedono Madiun with a BOR rate of 66.19% is 219 people. In conclusion, there are differences in calculating the need for nurses in the Nina Formula Method and the Ilyas Formula Method. The calculation results from the Nina Formula method are close to the need for nurses at dr. Soedono Madiun at this time. Keywords: BOR, Calculation of Personnel Requirements, Nurse Planning